2006
DOI: 10.1182/blood-2005-09-3624
|View full text |Cite
|
Sign up to set email alerts
|

Long-term acyclovir for prevention of varicella zoster virus disease after allogeneic hematopoietic cell transplantation—a randomized double-blind placebo-controlled study

Abstract: Varicella-zoster virus (VZV) disease occurs in 30% of allogeneic hematopoietic cell transplant recipients who had a history of VZV infection. A safe and effective prevention strategy has not been established. In a double-blind controlled trial, 77 hematopoietic cell transplant recipients at risk for VZV reactivation were randomized to acyclovir 800 mg twice daily or placebo given from 1 to 2 months until 1 year after transplantation. VZV disease at 1 year was the primary end point; VZV disease after discontinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
185
2
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(200 citation statements)
references
References 38 publications
(68 reference statements)
5
185
2
4
Order By: Relevance
“…The incidence of HZ at 1 year following SCT was reported to vary between 5 and 53%, 4,17,19,22,23 and specifically after autologous SCT between 8 and 30%. 3,[12][13][14][15][16] The increased risk of HZ in SCT recipients is highest during the first year following transplantation because of the diminished T-cell Varicella zoster virus reactivation C Kamber et al immunity, 3,12,15 and reaches a plateau by 2 or 3 years after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of HZ at 1 year following SCT was reported to vary between 5 and 53%, 4,17,19,22,23 and specifically after autologous SCT between 8 and 30%. 3,[12][13][14][15][16] The increased risk of HZ in SCT recipients is highest during the first year following transplantation because of the diminished T-cell Varicella zoster virus reactivation C Kamber et al immunity, 3,12,15 and reaches a plateau by 2 or 3 years after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[17][18][19][20] Clearly, live attenuated VZV vaccination is contraindicated in severely immunocompromised patients undergoing ASCT. In general, patients routinely receive oral antiviral prophylaxis after ASCT to reduce the risk of herpes virus-associated diseases, including HZ.…”
Section: Introductionmentioning
confidence: 99%
“…Two patients died from disseminated varicella zoster infection. Boeckh et al 54 recently showed that 800 mg acyclovir given b.i.d. for 12 months effectively prevented zoster reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the identified risk factors have previously been shown to be correlated. Acute GVHD increases the risk of CMV infection, 54,55 the CMV viral load 56 and subsequent chronic GVHD. 38,40 The use of alternative donors increases the risk of CMV infection and acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term acyclovir prophylaxis is effective in preventing reactivation. [24][25][26] Most episodes of herpes zoster in the absence of acyclovir prophylaxis occur within the first 2-10 months after transplantation and T-cell responses to VZV Ag encountered pretransplant can be detected as early as 1-6 months post transplant. 23,27 Therefore, vaccination of both donors and recipients could be a strategy worth studying further.…”
Section: Varicellamentioning
confidence: 99%